New dental and postcranial material of Agerinia smithorum (Primates, Adapiformes) from the type locality Casa Retjo-1 (early Eocene, Iberian Peninsula). Issue 113 (December 2017) - Femenias-Gual, Joan; Marigó, Judit; Minwer-Barakat, Raef; Moyà-Solà, Salvador
Abstract: New material attributed to Agerinia smithorum from Casa Retjo-1 (early Eocene, NE Iberian Peninsula), consisting of 13 isolated teeth and a fragment of calcaneus, is studied in this work. These fossils allow the first description of the calcaneus and the upper premolars for the genus Agerinia, as well as the first description of the P2 and M 2 for A. smithorum . The newly recovered lower teeth are virtually identical to the holotype of A. smithorum and are clearly distinguishable from the other species of Agerinia . The upper teeth also show clear differences with Agerinia marandati . The morphology of the calcaneal remains reveals that A. smithorum practiced a moderately active arboreal quadrupedal mode of locomotion, showing less leaping proclivity than notharctines but more than asiadapids. All the morphological features observed in the described material reinforce the hypothesis of a single lineage consisting of the species A. smithorum, A. marandati, and Agerinia roselli . Furthermore, the phylogenetic analysis developed in this work, which incorporates the newly described remains of A. smithorum, maintains the position of Agerinia as closely related to sivaladapids and asiadapids.